Design of a web portal for assertive diagnosis and cognitive evolution in children with special abilities - Meneses Claudio, Brian Andreé (2023)
A world beyond the five senses is what opens the doors to new expectations for children with special abilities, as they lack a variety of factors due to a prejudiced society with middle-aged life stereotypes. We will use the SCRUM method to make the appropriate changes in a short time this established to norms and laws both in education and health, what we develop is a web application that generates a diagnosis for cognitive evolution in children with special abilities. The number of special children who tried the software have made great strides in terms of individual performance. The studies carried out serve the teachers as health professionals who attend to the child with a report, in order to also contribute to the individual and social improvement that the children with special abilities will present through the therapies they need.